2+δ‐Dimensional Materials via Atomistic Z‐Welding. Issue 32 (11th September 2022) - Sahu, Tumesh Kumar; Motlag, Maithilee; Bandyopadhyay, Arkamita; Kumar, Nishant; Cheng, Gary J.; Kumar, Prashant
Abstract: Pivotal to functional van der Waals stacked flexible electronic/excitonic/spintronic/thermoelectric chips is the synergy amongst constituent layers. However; the current techniques viz. sequential chemical vapor deposition, micromechanical/wet‐chemical transfer are mostly limited due to diffused interfaces, and metallic remnants/bubbles at the interface. Inter‐layer‐coupled 2+ δ ‐dimensional materials, as a new class of materials can be significantly suitable for out‐of‐plane carrier transport and hence prompt response in prospective devices. Here, the discovery of the use of exotic electric field ≈10 6 V cm − 1 (at microwave hot‐spot) and 2 thermomechanical conditions i.e. pressure ≈1 MPa, T ≈ 200 °C (during solvothermal reaction) to realize 2+ δ ‐dimensional materials is reported. It is found that Pz Pz chemical bonds form between the component layers, e.g., CB and CN in G‐BN, MoN and MoB in MoS2 ‐BN hybrid systems as revealed by X‐ray photoelectron spectroscopy. New vibrational peaks in Raman spectra (BC ≈1320 cm –1 for the G‐BN system and MoB ≈365 cm –1 for the MoS2 ‐BN system) are recorded. Tunable mid‐gap formation, along with diodic behavior (knee voltage ≈0.7 V, breakdown voltage ≈1.8 V) in the reduced graphene oxide‐reduced BN oxide (RGO‐RBNO) hybrid system is also observed. Band‐gap tuning in MoS2 ‐BN system is observed. Simulations reveal stacking‐dependent interfacial charge/potential drops, hinting at the feasibility of next‐generation functional devices/sensors. Abstract : Novel 2+ δ ‐dimensional materials which are a new class of chemically bonded heterogenous 2D materials are synthesized for the first time.